Regional developments [in 2022 Global Food Policy Report] - Njuki, Jemimah; Benin, Samuel; Marivoet, Wim; Ulimwengu, John M.; Mwongera, Caroline; Breisinger, Clemens; Elmahdi, Amgad; Kassim, Yumna; Perez, Nicostrato D.; Akramov, Kamiljon T.; Djumaboev, Kahramon; Romashkin, Roman; et al. (International Food Policy Research Institute, 2022)
Climate change is a truly global threat, but its impacts differ around the world. Regions and countries urgently need to identify and implement policy responses that reflect local needs and opportunities. This section examines the effects of climate change on national and regional food systems in Africa, the Middle East and North Africa, Central Asia, South Asia, East and Southeast Asia, and Latin America and the Caribbean. For each major region, promising innovations and policy directions to promote the resilience and sustainability of food systems are considered: - Scaling up social protection programs in Africa south of the Sahara - Strengthening the focus on climate adaptation in Africa - Rethinking water use in the Middle East and North Africa - Promoting climate-smart practices and crop diversification in Central Asia - Reforming agricultural support policies in South Asia - Improving financing for climate change mitigation and adaptation in East and Southeast Asia - Supporting global food security and sustainability in Latin America and the Caribbean